DETERMINAN HARGA SAHAM PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Ainul Yusna Harahap; Anggi Sari Tambunan; Tuti Meutia (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2026)
This study aims to examine the influence of Return On Asset (ROA), Return On Equity (ROE), and Earning Per Share (EPS) on stock prices in food and beverage companies listed on the Indonesia Stock Exchange (IDX). The population of this study is food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the period 2015-2024. The sampling method in this study is by the purposive sampling method, from 95 food and beverage companies listed on the Indonesia Stock Exchange, 18 companies were sampled. The data sources in this study are secondary data obtained from www.idx.co.id websites, investment websites and the official websites of each company that is a sample. This study uses multiple linear regression analysis with this data management using SPSS software. The results of this study show that the variables Return on Asset (ROA) and Earning per Share (EPS) partially affect stock prices. Meanwhile, the Return on Equity (ROE) variable partially has no effect on the stock price. However, the variables Return on Asset (ROA), Return on Equity (ROE), and Earning per Share (EPS) simultaneously affect stock prices. This study still has limitations because it only uses profitability variables, namely ROA, ROE, and EPS. Therefore, the researcher then uses various independent variables so that the results of the research are different, more convincing, and more in-depth.